What color is your parachute?, 2012 - Bolles, Richard Nelson (Berkeley, CA : Ten Speed Press, 2012)
From Barnes & Noble: It began as a seventies word-of-mouth bestseller; now, forty years later, with ten million copies sold, Richard Bolles' What Color Is Your Parachute ranks as the most popular job-hunting book in the history of the world. Sharpened from year to year and decade to decade, this carefully conceived 384-page guidebook contains the current information you need to use Internet job-search and online social media sites more efficiently. In addition, readers can tap an update version of the book's valuable Transferable Skills Inventory and job-field exercises. A treasure trove for recent graduates and career-changers alike.
Preface: 40th Anniversary Edition of This Book -- Grammar and language note -- Introduction: -- How to find hope -- Survival skills you most need in today's world -- Attitudes Necessary For Survival: -- Three attitudes necessary for survival -- How to deal with handicaps -- Advanced Job-Finding Techniques: -- Best and worst ways to look for those job vacancies that are out there -- Do i really need a resume? -- Networking in this age of social media -- Sixteen tips about interviewing -- Six secrets of salary negotiation -- Advanced Job-Creation Techniques: -- Starting your own business -- Being inventive is key to survival -- How to choose a new career -- Inventory Of What You Have To Offer The World: -- Self-inventory (the flower exercise) -- What skills do you most enjoy using? -- Where do you want to use those skills? -- How do you find the name of that kind of job (or jobs)? -- Each One Teach One: -- Teaching survival job-hunting to others -- Pink Pages: -- Appendix A: Finding your mission in life -- Appendix B: Guide to dealing with unemployment depression -- Appendix C: Guide to choosing a career coach or counselor -- Appendix D: Sampler list of coaches -- About the author -- Index -- Update 2012 -- Foreign Editions -- Additional helpful resources from the author -- Books -- Workshops -- Online course.
"A practical manual for job-hunters and career-changers, 2012"--Cover.
Includes bibliographical references and index.
Keywords: Job hunting; Job hunting -- Computer network resources; Vocational guidance; Career changes; Applications for positions; Vocational guidance; Job hunting